Efektivitas Pembelajaran Berbasis Game Interaktif Brainzy Pada Hasil Belajar Matematika Siswa Kelas 1 Sekolah Dasar - Ari Aprilia Dwiana; Muslim (Jurnal Teknologi Informasi (JUTECH), 2025)
This study aims to determine the effectiveness of the educational game application Brainzy in improving mathematics learning outcomes of first-grade students at SDN 013 Rambah. The research employed a quantitative approach with a quasi-experimental design using a one-group pretest-posttest model. The research instrument consisted of pretest and posttest assessments administered to 27 students before and after the treatment. Descriptive statistical analysis revealed an increase in the average score from 61.67 (pretest) to 78.44 (posttest). The normality test indicated that the data were normally distributed, allowing further analysis using a paired sample t-test, which showed a significant difference between pretest and posttest scores (p < 0.05). Moreover, the N-Gain analysis yielded an average of 0.438, categorized as moderate. These findings suggest that the use of Brainzy is moderately effective in enhancing elementary students’ mathematics learning outcomes.